Factors influencing quality of life in extratemporal lobe epilepsy and mesial temporal lobe epilepsy: a cross-sectional study using medical records - Annaka, Hiroki; Nomura, Tomonori; Hasegawa, Naoya (Frontiers in Neurology, 2024)
Objective: This study aimed to examine differences in factors influencing quality of life (QOL) in people with extratemporal lobe epilepsy (ETLE) and mesial temporal lobe epilepsy (MTLE).We obtained data from the medical records of 84 (47 ETLE and 37 MTLE) people with epilepsy. The data included age, sex, employment, seizure frequency, number of antiseizure medication (ASM), Neurological Disorders Depression Inventory for Epilepsy (NDDI-E) score, and Quality of Life in Epilepsy Inventory-31 (QOLIE-31) score. Multiple regression analyses were performed using QOLIE-31 as the dependent variable and age, sex, employment, seizure frequency, number of ASM, and NDDI-E score as the independent variables in ETLE or MTLE.From the results of the multiple regression analyses, QOLIE-31 in ETLE was associated with NDDI-E (β = -0.757, p < 0.001) and employment (β = 0.388, p = 0.008). Meanwhile, QOLIE-31 in MTLE was associated with NDDI-E (β = -0.625, p < 0.001), employment (β = 0.396, p = 0.041), and number of ASMs (β = -0.399, p = 0.018). Conclusions: Overall, our findings indicate that the number of ASMs is potentially an influence on QOL of MTLE but similar effect is not observed in ETLE.